Physicochemical quality of water from Chuho springs, Kisoro district, Uganda - Nkurunziza, Gerald; Omara, Timothy; Nakiguli, Caroline Kiwanuka; Mukasa, Paul; Byamugisha, Denis; Ntambi, Emmanuel (My University, 2021)
In the current study, water from Chuho springs used as the main water source in Kisoro municipality, Uganda were assessed for their suitability as drinking water. The temperature, turbidity, conductivity, total dissolved solids, dissolved oxygen, biological oxygen demand, total hardness, total alkalinity, calcium, magnesium, phosphates, iron, copper, arsenic, chlorides and the fluoride content of the water samples were determined. Not all the parameters met World Health Organizations’ guidelines for drinking water. Temperature, dissolved oxygen and fluorides were outside the recommended limits of 15 ℃, 10-12 mg/L and 1.5 mg/L, respectively. Further studies should assess the microbiological and sanitary profile of the springs. __________________________________
Keywords: pH, temperature, conductivity, trace metals, water quality index.